An Analysis of Project Based Learning Application in Curriculum 2013 - Wisudawaty, Umi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2024)
This paper describes how project-based learning application in the classroom towards Curriculum 2013. A brief analysis on how project-based learning as a learning method especially in teaching English for senior high school students in curriculum 2013 will be applied in this paper. In addition, Curriculum 2013 requires teachers to apply various scientific approaches to engage students' activeness and maximize their ability in acquiring the materials. As one of them is project-based learning. This paper applied qualitative descriptive method, which analyzes how the project-based learning will affect students' performance in learning English on senior high school students in 2013 curriculum. The writer analyzes several research that has been applied in the classroom towards the project-based learning application. The result shows that project-based learning improved and significantly influenced students' speaking ability, reading comprehension, writing ability, classroom activity, and critical thinking.